A Modified Multi-Winding DC-DC Flyback Converter for Photovoltaic Applications - Pesce, Cristian; Riedemann, Javier; Pena, Ruben; Degano, Michele; Pereda, Javier; Villalobos, Rodrigo; Maury, Camilo; Young, Hector; Andrade Aguero, Ivan Eric (My University, 2021)
Featured Application This topology is applied to photovoltaic generation conversion using multiple panels and a single magnetic core, using MPPT and obtaining an efficiency over 96%. DC-DC power converters have generated much interest, as they can be used in a wide range of applications. In micro-inverter applications, flyback topologies are a relevant research topic due to their efficiency and simplicity. On the other hand, solar photovoltaic (PV) systems are one of the fastest growing and most promising renewable energy sources in the world. A power electronic converter (either DC/DC or DC/AC) is needed to interface the PV array with the load/grid. In this paper, a modified interleaved-type step-up DC-DC flyback converter is presented for a PV application. The topology is based on a multi-winding flyback converter with N parallel connected inputs and a single output. Each input is supplied by an independent PV module, and a maximum power point tracking algorithm is implemented in each module to maximize solar energy harvesting. A single flyback transformer is used, and it manages only 1/N of the converter rated power, reducing the size of the magnetic core compared to other similar topologies. The design of the magnetic core is also presented in this work. Moreover, the proposed converter includes active snubber networks to increase the efficiency, consisting of a capacitor connected in series with a power switch, to protect the main switches from damaging dv/dt when returning part of the commutation energy back to the source. In this work, the operating principle of the topology is fully described on a mathematical basis, and an efficiency analysis is also included. The converter is simulated and experimentally validated with a 1 kW prototype considering three PV panels. The experimental results are in agreement with the simulations, verifying the feasibility of the proposal.
Keywords: dc-dc power conversion; solar energy; energy conversion; multi-winding flyback transformer